Media(ted) discourses and climate change : a focus on political subjectivity and (dis)engagement - Carvalho, Anabela (2010)
Research has shown that the media are the main source of information and the main factor shaping people’s awareness and concern in relation to climate change and therefore have an important role in setting the public agenda. As a key forum for the production, reproduction and transformation of the meaning of public issues, the media influence understandings of risks, responsibilities, as well as of the functioning of democratic politics. This article argues that the media also matter to citizens’ perception of their (potential) political agency or their political subjectivity. Media representations construct particular ‘subject positions’ for individuals and cultivate dispositions to action or inaction. The article discusses the importance of citizens’ political engagement with climate change and points out some aspects of media(ted) discourses that may constrain the perceived possibilities of participation in the politics of climate change. While engagement with climate change has multiple dimensions and a number of barriers have been identified through empirical studies, this article offers a critique of the role of the media in political engagement with the problem and suggests avenues for future research.